Pembinaan Karakter Di SD Muhammadiyyah 16 Surakarta - Aunaya, Ganik Zun; , Muhroji, S.E, M.Si, M.Pd (2017)
This study aims to describe: 1) Character building planning in SD Muhammadiyyah 16 Surakarta 2) The characters are developed in SD Muhammadiyyah 16 Surakarta 3) organization of construction building character in SD Muhammadiyyah 16 Surakarta 4) Implementation of character building in SD Muhammadiyyah 16 Surakarta 5) Evaluation of character building in SD Muhammadiyyah 16 Surakarta. This type of research is qualitative research (Qualitative Research). Data was collected through interviews, and supported by observation and documentation. The validity of the data using triangulation. Data analysis technique used by reduction, data display, and verification / conclusion . Coaching character is more dominant developed the character akhlakul karimah. Planning character building akhlakul karimah is done by creating lesson plans in teaching and learning, the development plan of the material in extracurricular activities, and create a program of short-term / long in the activities of the school culture. Implementation of character building akhlakul karimah in the mix with teaching and learning activities, extracurricular activities, and school culture.long in the activities of the school culture. Organizing conducted by the principal by dividing tasks in each classroom teachers to assist learners in the implementation of development activities character akhlakul karimah. Evaluation of the implementation of development activities character akhlakul karimah can use two strategies are the spontaneous evaluation, and evaluation by discussing.